2022
DOI: 10.3390/antibiotics11111466
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Gold Nanoflowers Using Rosmarinus officinalis and Helichrysum italicum Extracts: Comparative Studies of Their Antimicrobial and Antibiofilm Activities

Abstract: This study was concerned with the green synthesis of gold nanoflowers (AuNFs) using the bioactive constituents of Rosmarinus officinalis (rosemary) and Helichrysum italicum (immortelle) extracts, as reducer and stabilizer agents along with the determination of their antibacterial and antibiofilm activity against E. coli, S. aureus, and S. epidermidis. The AuNFs were characterized using STEM, UV–Vis, DLS, ZETA, FESEM-EDX, and FTIR techniques. The antibacterial and antibiofilm activity of the AuNFs were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 105 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Similar sizes were also previously reported by Borah et al using Syzygium cumini [39]. Onmaz et al reported sizes <100 nm NFs using Helichrysum italicum [40]. Other studies suggest that tannin-based polymers enhance reduction [41], explaining the unexpected formation of NFs from L discolor.…”
Section: Tem Particle Size and Zeta Potential Analysissupporting
confidence: 85%
“…Similar sizes were also previously reported by Borah et al using Syzygium cumini [39]. Onmaz et al reported sizes <100 nm NFs using Helichrysum italicum [40]. Other studies suggest that tannin-based polymers enhance reduction [41], explaining the unexpected formation of NFs from L discolor.…”
Section: Tem Particle Size and Zeta Potential Analysissupporting
confidence: 85%
“…Borah et al reported similar sizes using Syzygium cumini [39]. Onmaz et al reported NFs of sizes < 100 nm using Helichrysum italicum [40]. Other studies suggest that tannin-based polymers enhance reduction [41], explaining the unexpected formation of NFs from L. discolor.…”
Section: Tem Particle Size and Zeta Potential Analysismentioning
confidence: 94%
“…Over the last decade, several researchers have investigated the ethnopharmacological and ethnomedicinal properties of numerous plant-derived bioactive compounds and, recently, their antimicrobial and antibiofilm activities [ 35 ]. Several in vitro and in vivo experimental investigations revealed the therapeutic significance of numerous phytochemicals ( Table 1 ).…”
Section: Plant-derived Bioactive Compounds As Anti-cancerous Agentsmentioning
confidence: 99%